A coumarin based highly selective fluorescent chemosensor for sequential recognition of Cu2+ and PPi. Issue 49 (5th December 2018) - Meng, Xianjiao; Cao, Duanlin; Hu, Zhiyong; Han, Xinghua; Li, Zhichun; Liang, Dong; Ma, Wenbing
Graphical abstract: Highlights: A novel coumarin based chemosensor1 was synthesized with tren and quinoline as the receptors. The chemosensor1 can be used to sequential detect Cu 2+ and PPi in CH3 CN/HEPES buffer medium. The detection limits for Cu 2+ and PPi were estimated to be 1.9 × 10 −6 and 5.96 × 10 −8  M, respectively. Abstract: In this study, we have successfully synthesized a new coumarin based fluorescent chemosensor1, in which tren and quinolone are introduced as receptors for sequential recognition of Cu 2+ and PPi. The structure of chemosensor1 was characterized by 1 H NMR, 13 C NMR and ESI-HR-MS. Sensor1 showed an obvious "on-off" fluorescence quenching response toward Cu 2+, and the quenching efficiency reached a maximum of 99.6% with the addition of 20 equiv. of Cu 2+ . The1 -Cu 2+ complex showed an "off-on" fluorescence enhancement response toward PPi over many competitive anions, especially HPO4 2− and H2 PO4 − . The detection limit of sensor1 was 1.9 × 10 −6  M to Cu 2+ and 5.96 × 10 −8  M to PPi. In addition, sensor1 showed a 1:1 binding stoichiometry to Cu 2+ and sensor1 -Cu 2+ showed a 2: 1 binding stoichiometry to PPi in CH3 CN/HEPES buffer medium (9:1 v/v, pH = 7.4). The stable pH range of sensor1 to Cu 2+ and1 -Cu 2+ to PPi was from 4 to 8.